(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
In the casualty it is the duty of an Indian Medical Graduate to examine and record the details of medico legal cases and send intimation to the police. In emergency services sometimes the Indian Medical Graduate is not able to record the injury details of the patient due to lack of expertise, disinterest and sense of apprehension towards legal procedures. According to the new curriculum the Indian Medical Graduates study Forensic Medicine in the second and third year and during Internship they are again posted in Forensic Medicine to undergo medico legal training. In the Postgraduate curriculum of Forensic Medicine they have casualty postings. The number of postgraduates joining Forensic in various medical colleges is dropping at an alarming rate as it is considered as dead body science. Clinical Forensic Medicine (CFM) is the area of forensic medicine that relates to the medical examination and assessment of the living. It also has a significant public health and safety role. Research based on clinical forensic examination results have the potential to contribute to injury and death prevention. The aim of this article is to share the author’s experience in the Clinical Forensic Medicine unit.